5C Credit Analysis of Bad Debt of Finance Companies On The Momentum of The Holiday (Case Study: Company X For The 2021-2023 Period) - Andriyani, Yuli; Musa Budidarma, I Gusti Agung (Pelopor Publikasi Akademika, 2023)
The purpose of this study is to find out 5c credit analysis of bad debt of finance companies on the momentum of the holiday holiday. This study used descriptive analysis techniques designed and carried out by collecting data describing each variable before and after Hari Raya. The test results show that Character has a negative and significant effect on Astra Credit Companies (ACC) Non-Performing Financing (NPF). This can be proven by a calculated t of 4.999 greater than the table t (1.86) and a Sig value of 0.000 smaller than 0.05. Thus, it can be concluded that Hypothesis 1 (H1) is accepted that there is a negative and significant influence between the Character variable and the Non Performing Financing (NPF) of Astra Credit Companies (ACC). Conclusion based on the results of the study and the results of the analysis that has been carried out in previous studies, it can be concluded that the research data meets the criteria of data normality and is free from deviations from classical assumptions such as, Multicollinearity and Heteroscedasticity. So it has a high determination to be used as a prediction or forecasting